(untitled) (Journal of Rashid Latif Medical College, 2025)
Background: Diarrhea is a leading cause of childhood mortality worldwide. Timely interventions by caregivers play a crucial role in managing and preventing this condition. Aim: This study aimed to evaluate caregivers' knowledge and practices regarding the prevention of diarrheal diseases in children under the age of 5 years. Methods: A cross-sectional study was conducted from January to July 2023 using a convenience sampling technique. Data were collected from 158 caregivers of children under 5 years old using a self-structured, pre-tested questionnaire. Chi-square test was applied, and a p-value <0.05 was considered significant. Results: A total of 158 caregivers participated in the study. The mean age of respondents was 28.4 ± 7.6 years. Among them, 22.8% were illiterate, 84.2% were housewives, and 37.4% had an income exceeding 31,000 rupees/month. The majority (43.1%) had 'poor' knowledge, 24% exhibited 'poor' attitudes and practices, while 12% demonstrated good practices. Significant associations were observed between caregivers' knowledge and education (p-value=0.004), income (p-value=0.001), frequency of diarrhea in a child (p-value=0.053), and practices with education (p-value=0.039). Conclusion: This study highlights the relationship between caregivers' literacy levels and family income with improved knowledge and feeding practices in preventing diarrhea. It underscores the crucial role of caregivers in managing acute diarrheal diseases.